Configurations of entrepreneurial ecosystems: an analysis based on GEM data (Revista Brasileira de Inovação, 2024)
Entrepreneurial ecosystems (EEs) are receiving greater attention both in the academic world and in the field of government action. Recently, many studies have used a configuration perspective in the analysis of EEs. However, many of these studies have not specifically addressed whether different EE configurations can produce similar outputs; that is, they do not properly explore the concept of equifinality. Our main purpose was to fill this theoretical and empirical gap by exploring and demonstrating the patterns of performance of EEs (e.g., configurations) along a bundle of entrepreneurial outcome indicators. Using the Entrepreneurship Framework Conditions (EFCs) indicators provided by the Global Entrepreneurship Monitor (GEM) from 60 countries and applying exploratory factor analysis and cluster analysis, we identified and developed five distinctive EE configurations. Later, by applying analysis of variance (ANOVA) to compare these EE configurations across the entrepreneurial outcome indicators, we were able to show distinctive (dis)similarities with respect to the outcome indicators investigated. The results contribute to the understanding that there is not only one type of successful EE. In other words, the equifinality of EEs was empirically evidenced by our analysis. This is a significant theoretical contribution to the field, emphasizing the need for a broader view of how EEs may be configured and denying the relevance of searching for an ideal EE.